Recomposição performativa: expansão da liberdade criadora do performer em três processos colaborativos - Marina Carvalho Spoladore Rezende (2024)
This paper presents a proposal to expand the performer's creative freedom through the systematization of a methodology we call performative recomposition. This activity involves collaborative creation starting from a pre-existing composition. In this process, the performer works in partnership with composers or other performers, actively participating from the conception and development of pre compositional elements to the realization of the performance. The main objectives were to promote the performer's role within composition, moving beyond the role of merely receiving a score; to question the score as a mediator between creation and performance; to challenge the hierarchy between the functions of composition and performance, or between author and performer, as established in prevailing practices in concert music; to reflect on the notion of authorship and the concept of musical work itself; and to develop replicable co-creation proposals in performer training within academic environments. Based on definitions of recomposition and categories of collaboration, the theoretical and methodological framework of this work draws on Paulo de Assis' concept of the emancipated performer and Vera John-Steiner's notions of familiar, integrative, and complementary collaboration. The three case studies were conducted with composers Pauxy Gentil-Nunes and Marcílio Onofre, and pianist Joana Boechat, resulting respectively in the compositions: Jonas Reborn (2022), based on Jonas (1992) by Pauxy Gentil-Nunes; Mirageiras (2024), based on Miragem (2009) by Marisa Rezende; and Odradek: traquinices imaginadas (2024), based on Odradek (2010) by Valéria Bonafé. The different work dynamics were guided by a global methodology divided into three stages: material reception, experimentation, and performance realization. The unique characteristics of each case study contributed to the development of methodologies for performative recomposition and the fusion of creation and performance.